Photocatalytic degradation of carbamate insecticides: effect of different parameters (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
Photocatalytic degradation of a model compound of the carbamate insecticidecarbofuran in water was studied using polychromatic light and ZnO and TiO2 catalysts.The influence of operational parameters, such as reaction time and initial carbofuranconcentration, on photocatalytic degradation was studied. A pseudo-first-order kineticmodel was established and an almost complete removal of 88.4 mg L–1 of carbofuranoccurred within 2 h under optimized conditions. The reactions were examined by UVspectroscopy and high performance liquid chromatography (HPLC). In addition,the photocatalytic efficiencies of ZnO and TiO2 were compared under the samereaction conditions.
Keywords: carbofuran model compound; photocatalysis; zinc oxide; titan dioxide; kinetics